2017
DOI: 10.4018/ijesma.2017040104
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Applications in Shopping

Abstract: This exploratory paper focuses on the use of mobile applications in shopping from the customer activation point of view. Empirical survey data was collected from 23 mobile shopping application users, and the major findings indicate that mobile applications present a modern and flexible channel for supporting and intensifying customer participation. However, in order to guarantee a long-term customer relationship, the application must be integrated with the service development and refinement activities of a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Past research clarifies the factors that encourage purchasing via the app and the intention to purchase the brand powering the app (when the app is linked to an existing offline or online brand). In terms of factors that encourage purchases via the app vs. other channels, extant studies identify the importance of positive customer experiences , especially the speed of transactions, security and user-friendliness that apps can provide (Buellingen and Woerter 2004 ; Figge 2014 ); consumer participation, flexibility and technology quality (Mäki and Kokko 2017 ; Dacko 2017 ); location awareness and interactivity (Wang et al 2016a ); and access to information and promotions (Magrath and McCormick 2013 ). Extant research also discusses the relevance of the customer’s overall interest in the app (Taylor and Levin 2014 ) and specific apps’ attributes (e.g., ease of use and connection with the self) as drivers of the intention to purchase via the app over the physical store (Newman et al 2018 ), often due to heightening buying impulses (Wu and Ye 2013 ; Chadha, Alavi and Ahuja 2017 ).…”
Section: Adoption Stagementioning
confidence: 99%
“…Past research clarifies the factors that encourage purchasing via the app and the intention to purchase the brand powering the app (when the app is linked to an existing offline or online brand). In terms of factors that encourage purchases via the app vs. other channels, extant studies identify the importance of positive customer experiences , especially the speed of transactions, security and user-friendliness that apps can provide (Buellingen and Woerter 2004 ; Figge 2014 ); consumer participation, flexibility and technology quality (Mäki and Kokko 2017 ; Dacko 2017 ); location awareness and interactivity (Wang et al 2016a ); and access to information and promotions (Magrath and McCormick 2013 ). Extant research also discusses the relevance of the customer’s overall interest in the app (Taylor and Levin 2014 ) and specific apps’ attributes (e.g., ease of use and connection with the self) as drivers of the intention to purchase via the app over the physical store (Newman et al 2018 ), often due to heightening buying impulses (Wu and Ye 2013 ; Chadha, Alavi and Ahuja 2017 ).…”
Section: Adoption Stagementioning
confidence: 99%
“…In the specific instance of mobile apps, past research has seldom considered the influence of past behavior and, when accounting for it, it has been considered primarily as a determinant of apps' adoption and initial use. For example, a few studies have highlighted as important drivers of apps' discovery and use: (a) mobile experience and browsing behavior (e.g., Kim et al, 2017); (b) acquisition frequency and recency (Liu et al, 2017); (c) usage frequency and recency (Newman et al, 2018;Viswanathan et al, 2017); and (d) active app usage or consumer voluntary participation (Chung, 2015;Mäki & Kokko, 2017). Moreover, empirical studies based on the analysis of panel data revealed that many categories of apps are characterized by high levels of usage concentration.…”
mentioning
confidence: 99%